Characterization and treatment monitoring of ureagenesis disorders using stable isotopes - Gabriella Allegri; Martin Poms; Nadia Zürcher; Véronique Rüfenacht; Nicole Rimann; Déborah Mathis; Beat Thöny; Matthias Gautschi; Ralf A. Husain; Daniela Karall; Karolina Orchel-Szastak; Francesco Porta; et al. (npj Metabolic Health and Disease)
Abstract Urea cycle disorders (UCDs) are a group of rare conditions, possibly life-threatening and without definitive cure besides liver transplantation. Traditional biochemical analyses/biomarkers cannot reliably determine changes in the UC-function from baseline to post-intervention. We describe a UHPLC-HRMS method to assess ureagenesis in plasma and dried blood spots for [15N]urea and [15N]amino acids, using [15N]ammonium chloride as tracer. [15N]enrichment of urea and amino acids was studied in controls (n = 22) and patients (n = 59), the latter showing characteristic ureagenesis variations according to their underlying metabolic defect. Follow-up of therapies was successful, as we observed restoration of [15N]urea production and lowering of [15N]glutamine. There were no adverse events, and only minimal amounts of tracer and samples required with a short sample preparation time and analysis. Thus, the method proved to be safe and efficient to monitor UCD patients of variable severity pre- and post-therapy, being suitable as physiological endpoint for development of therapies.